A series of meta-analytic tests of the depletion effect: Self-control does not seem to rely on a limited resource - Carter, Evan C; Kofler, Lilly M; Forster, Daniel E; McCullough, Michael E (Journal of experimental psychology. General, 2015)
Failures of self-control are thought to underlie various important behaviors (e.g., addiction, violence, obesity, poor academic achievement). The modern conceptualization of self-control failure has been heavily influenced by the idea that self-control functions as if it relied upon a limited physiological or cognitive resource. This view of self-control has inspired hundreds of experiments designed to test the prediction that acts of self-control are more likely to fail when they follow previous acts of self-control (the depletion effect). Here, we evaluated the empirical evidence for this effect with a series of focused, meta-analytic tests that address the limitations in prior appraisals of the evidence. We find very little evidence that the depletion effect is a real phenomenon, at least when assessed with the methods most frequently used in the laboratory. Our results strongly challenge the idea that self-control functions as if it relies on a limited psychological or physical resource.